Blood-Brain Barrier ABC-transporter P-glycoprotein in Alzheimer's Disease: Still a Suspect? - M.E. van Assema, Danielle; N.M. van Berckel, Bart (Current Pharmaceutical Design, 2016)
Alzheimer’s disease is a neurodegenerative disorder and the most common form of dementia. One of the pathological hallmarks of the disease is amyloid deposition in the brain. The major cause of amyloid deposition in sporadic Alzheimer’s disease is thought to be decreased brain clearance of amyloid. There is compelling preclinical evidence that the blood-brain barrier, a structure that maintains homeostasis in the central nervous system and protects the brain from harmful substances, plays an important role in amyloid clearance. Indeed, several dedicated transporter systems are present at the blood-brain barrier which may have a role in brain amyloid clearance, such as P-glycoprotein (P-gp). In vitro experiments and animal studies indicated increased amyloid deposition when P-gp was eliminated by pharmacological blockade or by genetic modification. And as decreased P-gp expression has been found in AD brains, P-gp became more and more a suspect. Using an imaging technique called positron emission tomography, P-gp transporter function was found to be decreased in Alzheimer’s disease patients compared to healthy controls, further establishing the important role of P-gp in the pathogenesis of the disease. In this review, we summarize what is now known about P-gp in Alzheimer’s disease pathology, as these transporters may provide a novel target for therapeutic strategies.
Keywords: ABC transporters